It Looks Like TB but is not TB - Bizanjo, Mahwash; Salahuddin, Naseem (Infectious Diseases Journal of Pakistan, 2023)
Mycobacterium Abscessus lung infection has a chronic, complicated indolent course with limited treatment options and poor outcomes. We present case of a young female who was treated as a case of pulmonary tuberculosis on the basis of symptoms, radiological findings and positive sputum smears for AFB and negative GeneXpert. She was declared as treatment failure, sputum cultures were sent which showed growth of NTM. Speciation showed Mycobacterium abscessus, treatment regimen was made according to drug susceptibility testing. Key Words: Non tuberculosis mycobacteria (NTM), a typical mycobacteria, Mycobacterium abscessus, Mycobacteria other than tuberculosis, Clinical presentation of NTM